Diseño de un centro deportivo recreacional biomimético para personas con discapacidad física en Quevedo - Suárez Loor, Bruno Eduardo (2024)
The purpose of this architectural project is to mitigate the scarce presence of safe and accessible sports and recreational spaces in the San Camilo parish of Canton Quevedo, with the aim of strengthening community dynamics and increasing the wellbeing of the residents. To achieve this goal, we seek to create accessible areas for the development of integrated communities, because these places improve social interaction and contribute to collective comfort. The priority is to develop an architectural project for a Recreational Sports Center that is accessible to all types of users, because, by eliminating architectural barriers, a more fluid pedestrian access is achieved, in addition, a multifunctional design is sought, that is, that has spaces that can be used to practice all types of sports.......